2016
DOI: 10.1007/s10120-016-0644-y
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of function-preserving gastrectomy for early gastric cancer: a multicenter propensity score matched cohort analysis comparing pylorus-preserving gastrectomy versus conventional distal gastrectomy

Abstract: Objective This study aimed to clarify the oncological safety of pylorus-preserving gastrectomy (PPG) compared with conventional distal gastrectomy (DG). Methods From three institutions specializing in cancer, the medical records for a cohort of 2898 consecutive patients who had undergone DG (n = 2208) or PPG (n = 690) for clinical stage I gastric cancer between January 2006 and December 2012 were analyzed. A propensity score for each patient was estimated on the basis of 38 preoperative clinical and tumor-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…Randomized controlled trials should resolve these clinical questions, and the Korean Laparoscopic Gastrointestinal Surgery Study (KLASS)-04, a multicenter randomized controlled trial which has been recruiting patients since July 2015, will determine the superiority of LAPPG to laparoscopic DG in postoperative QOL and survival rates of patients with EGC in the gastric midbody. Additionally, we recently reported the comparison of oncological outcomes with PPG and conventional DG for EGC in a multicenter propensity score-matched cohort analysis (20). Our findings indicated that the oncological safety of PPG for clinical T1N0 gastric cancer in the middle portion of the stomach was comparable to that of DG in cases with correctly estimated clinical tumor stage by the statistical method.…”
Section: Oncological Safety Of Ppgmentioning
confidence: 68%
See 1 more Smart Citation
“…Randomized controlled trials should resolve these clinical questions, and the Korean Laparoscopic Gastrointestinal Surgery Study (KLASS)-04, a multicenter randomized controlled trial which has been recruiting patients since July 2015, will determine the superiority of LAPPG to laparoscopic DG in postoperative QOL and survival rates of patients with EGC in the gastric midbody. Additionally, we recently reported the comparison of oncological outcomes with PPG and conventional DG for EGC in a multicenter propensity score-matched cohort analysis (20). Our findings indicated that the oncological safety of PPG for clinical T1N0 gastric cancer in the middle portion of the stomach was comparable to that of DG in cases with correctly estimated clinical tumor stage by the statistical method.…”
Section: Oncological Safety Of Ppgmentioning
confidence: 68%
“…Several retrospective reports with relatively a great many patients who underwent PPG consistently showed the oncological safety of PPG (17)(18)(19)(20)(21). PPG procedures that were evaluated those that preserved the nerve system and blood flow supply to the pyloric antrum for maintenance of the pyloric function, which resulted in incomplete lymph node dissection of the suprapyloric and infrapyloric lymph nodes.…”
Section: Oncological Safety Of Ppgmentioning
confidence: 99%
“…Nonetheless, PPG, as a typical function-preserving gastrectomy, has been demonstrated to show further advantages in functional outcomes compared to distal gastrectomy in middle third EGC [7,28,29]. In addition, the oncological safety of PPG operation has been demonstrated in large retrospective studies [7,9,30]. To gain more evidence about the functional outcome, KLASS-04, a multicenter randomized-controlled trial comparing laparoscopic pylorus-preserving gastrectomy (LPPG) versus laparoscopic distal gastrectomy (LDG) for the middle third early gastric cancer has finished recruitment in Korea [11].…”
Section: Discussionmentioning
confidence: 99%
“…1 3 rate. For early gastric cancer, surgeons started to consider functional preserving gastrectomy to improve the functional outcome and quality of life (QOL) without compromising oncological safety [5][6][7][8][9][10]. Pylorus-preserving gastrectomy (PPG) is such kind of function-preserving surgery, which has gained popularity in East Asian countries [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is a kind of tumor with high morbidity and mortality [1]. Although surgical treatment, chemotherapy and radiotherapy could greatly improve the survival of patients with gastric cancer, which could not be cured or recurred within several years [2].…”
Section: Introductionmentioning
confidence: 99%